2016
DOI: 10.22456/1679-9216.81302
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Neoplasm in Dogs

Abstract: Background: Various diseases can cause spinal cord disorders in dogs including neoplasia of the nervous system, which are more common in mature and older animals. Some breeds, as brachycephalics, are more predisposed for certain types of tumors. Spinal neoplasia can be categorized as primary or secondary tumors, and still can be grouped in extradural, intradural/extramedullary or intramedullary. The aim of this study was to investigate the signalment, neurological syndrome, type and source of the mass, presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…A report by Egenvall et al (2007) revealed an incidence rate of 9% for malignant bone tumours localised to the vertebrae in Swedish dogs. Moreover, various diseases, including neoplasia, cause spinal cord disorders in dogs, resulting in symptoms, such as ataxia, paraparesis, paraplegia, tetraparesis, and tetraplegia (Bagley 2010;Valentim et al 2016). The range and severity of these symptoms also depend on several factors: the spinal region affected, localisation with respect to the spinal cord, cell type, malignancy, and compression rate (Seguin et al 2000;North and Banks 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A report by Egenvall et al (2007) revealed an incidence rate of 9% for malignant bone tumours localised to the vertebrae in Swedish dogs. Moreover, various diseases, including neoplasia, cause spinal cord disorders in dogs, resulting in symptoms, such as ataxia, paraparesis, paraplegia, tetraparesis, and tetraplegia (Bagley 2010;Valentim et al 2016). The range and severity of these symptoms also depend on several factors: the spinal region affected, localisation with respect to the spinal cord, cell type, malignancy, and compression rate (Seguin et al 2000;North and Banks 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Malignant tumours can spread throughout the body. Although the lungs are the most common site for the distant metastasis of canine mammary cancer, metastasis to the skeletal system, including the vertebral bone, occasionally occurs (Cooley and Waters 1998;Valentim et al 2016). Specifically, metastatic neoplasms account for 65% of spinal tumours in dogs, predominantly originating from the mammary gland (Valentim et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ocorrência de metástases para a coluna vertebral já foi relatada anteriormente em casos de carcinomas mamários, pancreáticos e prostáticos de cães [12] e no epitélio transicional da uretra de cães e felinos [3,11], na maioria das vezes cursando com infiltração na músculatura e nas vértebras adjacentes. Em ambos os casos deste relato notou-se acentuada deformidade das estruturas ósseas acometidas pela metástase, esse fato não é claro nestes relatos, visto que muitos deles apresentam casos de tumores intradurais, epidurais e/ou na medula espinhal, sem associação com a estrutura óssea vertebral [11,17].…”
Section: Discussionunclassified
“…Os sinais neurológicos foram mais acentuados no paciente do caso 2, em que houve compressão de segmentos medulares torácicos, levando a lesões importantes de neurônio motor superior. Relatam-se casos de meningiomas no canal medular de cães, promovendo compressão entre T2 e T4, com sinais clínicos similares aos observados, como paralisia bilateral de membros pélvicos, apresentando boa resposta após o tratamento cirúrgico [17]. Aponta-se que esses tumores eram passíveis de remoção cirúrgica, diferenciando em muito da metástase observada no paciente supramencionado.…”
Section: Discussionunclassified